An approach for housing wealth estimation: The Mexican case - Ana Laura García; Juan Pedro González; Jhasua Velázquez (Banco de México, 2022)
Housing is the greatest asset held by most households, and it is an important determinant of their financing and consumption decisions. Despite the fact that measuring housing wealth is crucial for understanding households' economic behavior, this indicator is currently unavailable in Mexico due to the lack of data commonly required for its estimation. This paper proposes a more flexible methodology, based on the quantity times price approach and the perpetual inventory method, that eases data requirements while still meeting international guidelines. Our results suggest housing wealth in Mexico has followed an upward trend as percentage of GDP since 2005, reaching around 187% and 202% of GDP in 2020. In addition, our measure enables the calculation of other popular indicators concerning households, such as housing equity and household total net worth.
Keywords: G51; E21; E22; R2; R31; O18; 330; Housing; household wealth; perpetual inventory method; quantity times price approach